1968 ACADEMY MEETING - Dale, Ernest (Academy of Management Journal, 1968)
The article reports that the 1968 Academy of Management annual meeting will be held in Chicago, Illinois despite concerns over the earlier disturbances at the 1968 Democratic National Convention.